2013
DOI: 10.1080/02626667.2013.839874
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Japanese areas susceptible to snow cover change

Abstract: Many of the Japanese regions subject to seasonal snow cover are characterized by low elevations and relatively high winter temperatures. A small change in winter temperatures could render many of these areas susceptible to snow cover change and consequently affect water resources management. This paper describes a climatological approach combined with an AGCM output to identify the regions and main river basins most sensitive to snow cover change in the case of climate change in Japan. It was found that a 1• C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Teleconnections are statistical associations among climate variables separated by large distances and are a consequence of the large-scale dynamics of the ocean and atmosphere linking disparate regional climates into one unified, global climatic system [7,8]. Numerous studies have shown that climate variability has a strong impact on basin water resources through changes in hydrologic variables [9][10][11][12]. The glacier mass balance variability could be a reflection of low-frequency climatic fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Teleconnections are statistical associations among climate variables separated by large distances and are a consequence of the large-scale dynamics of the ocean and atmosphere linking disparate regional climates into one unified, global climatic system [7,8]. Numerous studies have shown that climate variability has a strong impact on basin water resources through changes in hydrologic variables [9][10][11][12]. The glacier mass balance variability could be a reflection of low-frequency climatic fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus among the scientific community is that as the climate warms, the number of snowfall/snow cover days and total accumulated snowfall will steadily SOLA, 2020, Vol. 16, 217-220(TBA), doi:10.2151/sola.2020 decrease as we approach the end of the century, particularly in areas of low elevation (Matsumura and Sato 2011;Chaffe et al 2013;Katsuyama et al 2020). What is less certain, is the effect climate change has on heavy to extreme snow events (O`Gorman 2014).…”
Section: Introductionmentioning
confidence: 99%